Agritourism and gender equality in developing economies - Zvavahera, Promise (Journal of Sustainable Tourism and Entrepreneurship, 2025)
Purpose: This study aims to investigate the role of agritourism in fostering women's empowerment and advancing gender equality in developing economies by assessing its capacity to create inclusive economic opportunities, enhance social status, and influence gender norms. Research Methodology: This study conducts an expansive literature review to examine agritourism's potential to promote gender equality and women's empowerment in developing economies, with Zimbabwe serving as the case study. Comprehensive searches were conducted across Scopus, PubMed, JSTOR, and Web of Science to gather pertinent data. Results: Gender disparities in economic participation, limited resources, inadequate market access, absence of land titles, and constrained decision-making constitute the primary challenges confronting women in agritourism. Nevertheless, given appropriate support, the emerging agritourism sector presents distinctive opportunities to address these challenges by establishing income-generating activities, promoting skills development, and empowering women in agritourism. Conclusions: Literature reveals that a few women own land for agritourism, limiting their economic engagement, empowerment, and decision-making. Gender-based discrimination, patriarchal norms, limited assistance, and finances limit their participation. Zimbabwe, like many developing nations, faces similar issues, highlighting the necessity for women's empowerment policies. Limitations: A key weakness of this study is the reliance on secondary data and the concentration on a single country, which may restrict the generalisability of the findings to other developing economies. Contribution: The insights presented in this study have the potential to shape policies and practices aimed at empowering women in rural Zimbabwe and beyond, fostering gender equality, and contributing to more sustainable and inclusive models of rural development.